On new records and distribution of ten species of the genus Lyssomanes Hentz from southern South America (Araneae: Salticidae: Lyssomaninae) - Galvis, William (2016)
On the basis of literature review and material examination of seven arachnological collections, the geographic distributions often species of Lyssomanes inhabiting Argentina and neighboring countries are provided, extending the known range of the genus in southern South America. New generic and specific records are presented from Brazil, Uruguay and Argentina.